2008
DOI: 10.1007/bf03346389
|View full text |Cite
|
Sign up to set email alerts
|

Normal age-dependent values of serum insulin growth factor-I: Results from a healthy Italian population

Abstract: Serum IGF-I levels were measured in 547 non-hypopituitaric, non-acromegalic healthy subjects of both sexes in Italy to develop reference values in relation to age and sex. Participant subjects were stratified in three age classes (25- 39, 40-59 and >or=60 yr) and IGF-I assay was carried out by double-antibody radio immunoassay. Pearson's correlation coefficient between age and IGF-I values was calculated by sex and predefined age ranges. IGF-I levels significantly decreased with age (p<0.001, Kruskal-Wallis te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…In liver diseases, serum level of IGF-1 is thought to provide a useful marker of the organ function, independently of etiology and patient age (20,24,42). In the CH-C group, our investigations confirmed the negative correlation between concentration of S-IGF-1 and patient age described by other authors (43,44). Moreover, in the CH-C group, we demonstrated that mean S-IGF-1 concentration is higher in women as compared to men.…”
Section: Discussionsupporting
confidence: 87%
“…In liver diseases, serum level of IGF-1 is thought to provide a useful marker of the organ function, independently of etiology and patient age (20,24,42). In the CH-C group, our investigations confirmed the negative correlation between concentration of S-IGF-1 and patient age described by other authors (43,44). Moreover, in the CH-C group, we demonstrated that mean S-IGF-1 concentration is higher in women as compared to men.…”
Section: Discussionsupporting
confidence: 87%
“…The maximum difference in the upper limit (97.5th percentile) was 7 µg/L (20 to 30 years) and the maximum difference in the lower limit (2.5th percentile) was 10 µg/L (21 to 25 years). Therefore, similar to previous studies (7)(8)(9)(10)(11)(12)(13)(14), the IGF-1 reference values are reported according to age group, without distinction between genders ( Table 2). The curves representing the 97.5th, 50th (median) and 2.5th percentiles of IGF-1 as a function of age are shown in figure 1.…”
Section: Resultssupporting
confidence: 80%
“…Many other studies also failed to demonstrate such difference and their results were reported without distinction between genders (7)(8)(9)(10)(11)(12)(13)(14). The hypothesis of a consistent and plausible difference between genders is also weakened by the fact that eventual small differences are not uniform, with some reporting higher IGF-1 levels in men or women depending on their age (10,15) or even on the assay used (10).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations